VALUASI EKONOMI OBJEK WISATA PEMANDIAN AIR PANAS IE SEUUM ACEH BESAR DENGAN PENDEKATAN TRAVEL COST - Yohannes M Simanjuntak; Raja Masbar (Jurnal Ilmiah Mahasiswa Ekonomi Pembangunan, 2020)
AbstractThis study aims to determine what factors affect the demand of visitors to the Ie Seuum hot spring tourist attraction and to find out how much the economic value of the Ie Seuum hot spring tourist attraction seen from the travel cost method. Variables in this study include demand for attractions or Visitor Rate (VR) and travel costs to attractions or Travel Cost (TC). The data used in this study are primary data, primary data obtained directly from respondents through interviews. The findings show that the consumer surplus of the Ie Seuum hot spring tourism object obtained from the integral calculation was Rp. 27.9. From the estimation results of the first regression model, it is produced that the variable cost of travel (TC) is not significant to the frequency of visits (VR), while the results of the estimation of the second regression model are generated that income shows significant results to the frequency of visits (VR). The Government of Aceh Besar Regency is expected to be able to pay attention to the Ie Seuum hot spring tourism object, especially to pay attention to what factors can increase the demand for attractions.Keywords: Travel Cost, Frequency of Visits, Consumer Surplus.